Ответ:
[tex]2cos\alpha[/tex]
Решение:
[tex]sin(\frac{\pi}{2}-\alpha)-sin(\pi-\alpha)-cos(\pi-\alpha)-sin(2\pi-\alpha)=\\\\=cos\alpha -sin\alpha-(-cos\alpha)-(-sin\alpha)=\\\\=cos\alpha-sin\alpha+cos\alpha+sin\alpha=2cos\alpha[/tex]
***Для решения применялись формулы приведения
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex]2cos\alpha[/tex]
Решение:
[tex]sin(\frac{\pi}{2}-\alpha)-sin(\pi-\alpha)-cos(\pi-\alpha)-sin(2\pi-\alpha)=\\\\=cos\alpha -sin\alpha-(-cos\alpha)-(-sin\alpha)=\\\\=cos\alpha-sin\alpha+cos\alpha+sin\alpha=2cos\alpha[/tex]
***Для решения применялись формулы приведения